Urinary purine derivative excretion in swamp buffaloes after duodenal purine base infusion - Pimpa, O.; Liang, J.B.; Balcells, J.; Jelan, Z.A.; Abdullah, N. (Elsevier Science, 2003)
Four male swamp buffaloes (Bubalus bubalis) each fitted with a duodenal catheter, with an initial body weight of 244 ± 19.8 kg were used to study the recovery rate of urinary purine derivatives (PD) after duodenally infused with incremental amounts of purine bases (PB). During the experiment, the buffaloes were fed, at a maintenance energy level, a diet containing 40% oil palm frond and 60% concentrates (DM basis). Purine bases in the form of adenosine (50%) and guanosine (50%) were infused into the duodenum in five incremental rates equivalent to 0, 24, 47, 71 and 95 mmol purine per day. Urinary allantoin, the principal PD and uric acid were linearly correlated with PB input, while the contributions of other PD were not effected by treatments. The relationship between daily urinary PD (i.e. allantoin, uric acid) excretion (mmol) and duodenal PB infused (mmol per day) was Y = 0.12X + 12.78 (r2 = 0.45, P < 0.001), suggesting that only 12% of supplied exogenous PB were excreted in the urine. The intercept suggested that PD excreted at maintenance energy level was 12.8 mmol per day. Urinary PD excretion rate of swamp buffaloes was much lower than those reported for cattle. We postulate that the discrepancy between the two species of ruminants could be due to a lower rate of PD absorption in the small intestine and/or recycling of plasma PD in buffaloes.